Fun at smart partnership program - Chong, Ah Kow (Pusat Bahasa Moden dan Sains Kemanusiaan, 2012)
28 April 2012. A group of 30 UMP undergraduates and 30 primary students from Sekolah Jenis Kebangsaan Cina (SJKC), Gambang, were in exuberant mood as they indulged in language activities during the Smart Partnership Program. The program, organized by MLCC and Foreign Languages Department of CMLHS aimed to motivate the SJKC students in their study and to create an environment for UMP students presently attending Mandarin classes to practise the language.